Facing the Indonesian Media Conglomeration: Action of Preservation on Political Interest (Faculty of Communications Science, Dr. Soetomo University, 2017)
After 1999, Indonesia's Media became grown up. It is the implication of the fallen of the authoritarian regime, Suharto. The growth has another side effect about trends of media conglomeration. Indonesian Media Conglomerate such as Tanoesoedibjo, Tandjung, Paloh and Bakrie also have the background as a politician. Mass media are an efficient tool to change the mind of people. Mass society theory makes several basic assumptions about individuals, the role of media, and the nature of social change. Media owner used their media for preserving his political influences. Facing this situation, Indonesian regulation about media ownership ignored by media owners. They used their power in the political area to get away from the regulation. Whereas, in Indonesian Law Number 32, issued on 2002 about Broadcasting Media, Especially on Chapter 36 verse 4 states,